Community Service Program: Implementation of the "One Day Five Verses" Method in Memorizing the Qur'an - Muhammad Iqbal; Zaki Muhammad Fathullah; Bani Hibban; Muhammad Afkarul Watan; Muhammad Zaki Aslam; Rozaanah Rozaanah (As-sunnah: Jurnal Pengabdian Masyarakat, 2023)
The application of the "one day five verses" method is one of the forms and models used to memorize Al-Qur'an verses, especially at the children's level at SD IT An-Nur in Meunasah Lhok Village, Meureudu District, Pidie Jaya Regency. Superior program by implementing a system of memorizing five verses a day for students so that within a year, students are able to memorize one juz. The aims of this research are: 1) to find out how to memorize students using the "one day, five verses" method at SD IT An-Nur Pidie Jaya. 2) Determine the abilities and targets of students by implementing the "one day, five verses" method at SD IT An-Nur Pidie Jaya. In this research, researchers used descriptive qualitative research methods with a case study approach. Then, data collection was carried out through interviews, observation, and documentation. The background of the research method is to make it easier to obtain the desired data and sources and to obtain precise and accurate information. The results of research on the "one day, five verses" method at SD IT An-Nur Pidie Jaya show that running and implementing this memorization system works well. Every morning before learning begins in class, students are required to give or deposit their memorization to their respective class teachers.